Wood adhesive based on alkali-dissolved chitosan and preparation and application thereof
Patent Information
- Application Number
- CN202610943011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]综上所述,现有技术存在以下关键不足:酸体系下易对胶合性能的耐久性及后续金属连接件的使用造成影响;未充分利用碱溶壳聚糖在碱性条件下的高反应活性氨基,以及碱溶壳聚糖与其他改性剂在碱性体系中的协同增效
[0018] (1) This invention employs an alkaline dissolution process to avoid the potential decomposition/corrosion of the wood substrate and metal connectors by the acid system; simultaneously, the alkaline environment enhances the amino reactivity of chitosan and improves the crosslinking efficiency of chitosan, soybean protein, and epichlorohydrin. Anhydrous calcium chloride is introduced to construct a chelating coordination network, which synergistically forms a hydrogen bond and hydrophobic interaction composite system with soybean protein, ultimately constructing a triple network of chemical crosslinking, coordination crosslinking, and physical entanglement. The plywood prepared with the finished adhesive meets the dry/wet strength requirements and fully satisfies the technical requirements of Class II plywood in the national standard (GB/T 9846-2015, ≥0.70MPa).
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wood adhesives, specifically relating to the preparation of a wood adhesive based on alkali-dissolved chitosan and its application in plywood. Background Technology
[0002] Wood adhesives are key materials in the engineered wood products industry. Currently, the dominant synthetic resin adhesives, such as urea-formaldehyde (UF), phenolic (PF), and melamine-formaldehyde (MF), all contain formaldehyde. During production and use, they release free formaldehyde, posing a threat to human health and the environment. With increasing environmental awareness and increasingly stringent environmental regulations, developing formaldehyde-free biomass-based wood adhesives has become an inevitable trend in the industry.
[0003] Chitosan is the most common natural alkaline polysaccharide, obtained by the deacetylation of chitin. It is widely available, renewable, biocompatible, biodegradable, and possesses natural antibacterial properties, showing great application potential in the field of wood adhesives. However, traditional methods of using chitosan have the following problems:
[0004] 1) Inherent drawbacks of acid dissolution processes: Chitosan typically needs to be dissolved in acidic solutions such as dilute acetic acid or hydrochloric acid before use. Under acidic conditions, the β-1,4-glycosidic bonds on the chitosan molecular chain are prone to acid-catalyzed hydrolysis, leading to a significant reduction in molecular weight and deterioration of mechanical properties. Furthermore, acidic adhesives can corrode wood substrates and metal connectors, reducing bonding durability; they may also introduce an acidic odor into the boards.
[0005] 2) Limitations of the application of alkali-soluble chitosan: In existing technologies, the alkali / urea system (such as NaOH / urea, LiOH / NaOH / urea) for dissolving chitosan is mainly used to prepare membrane materials and hydrogels (see CN102634040A, CN111518305A). There are no reports of its direct application in wood adhesives. These applications differ fundamentally from wood adhesives in terms of performance requirements, usage environment, and curing conditions.
[0006] 3) Limited use of crosslinking agents: Epichlorohydrin, as a chitosan crosslinking agent, is mainly used in the field of adsorbent materials such as microsphere preparation (see CN107325306A). In wood adhesives, it is often used in combination with polyamide polyamine epichlorohydrin resin (PAE), and chitosan needs to be acid-soluble first. Existing technologies do not fully utilize the high reactivity of free amino groups in chitosan under alkaline conditions.
[0007] In summary, the existing technology has the following key shortcomings: acidic systems can easily affect the durability of the adhesive properties and the use of subsequent metal connectors; it does not fully utilize the highly reactive amino groups of alkali-soluble chitosan under alkaline conditions, nor the synergistic effect of alkali-soluble chitosan and other modifiers in alkaline systems. Summary of the Invention
[0008] To address the aforementioned deficiencies in existing technologies, the present invention aims to overcome these shortcomings by providing an alkali-soluble chitosan-based multi-crosslinked wood adhesive. This adhesive directly dissolves chitosan using an alkali / urea freeze-thaw method, avoiding the protonation of chitosan amino groups under acidic conditions, thus enhancing its nucleophilic substitution reactivity and preventing degradation / corrosion of wood substrates and metal connectors under strong acid conditions. It utilizes the efficient ring-opening crosslinking of free -NH2 from chitosan with epichlorohydrin under alkaline conditions; introduces Ca²⁺ to form a chitosan-Ca²⁺ coordination network; denatures and expands soybean protein under alkaline conditions, forming a hydrogen-bonded / hydrophobic synergistic network with chitosan; and constructs a triple network structure of chemical crosslinking, coordination crosslinking, and physical entanglement, significantly improving adhesive strength and water resistance.
[0009] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows:
[0010] A wood adhesive based on alkali-dissolved chitosan, characterized in that, by mass parts, it comprises the following components: 30 parts chitosan alkali solution, 1-3 parts soy protein isolate, 0.5-1 parts epichlorohydrin, and 0.5 parts anhydrous calcium chloride.
[0011] In this invention, the application of alkali-dissolved chitosan raw materials to the preparation of wood adhesives is an original innovation. It avoids the decomposition / corrosion that acid systems may cause to wood substrates and metal connectors. At the same time, the alkaline environment can enhance the amino reactivity on the chitosan molecular chain and improve the crosslinking efficiency of chitosan, soybean protein and epichlorohydrin.
[0012] Furthermore, the chitosan alkaline solution is prepared by dissolving chitosan in an alkaline regulator and urea aqueous solution through 2-5 cycles of freeze-thaw (dissolution temperature: 20℃, freezing temperature: -20℃). The components by mass are: 1-5 parts chitosan, 2-5 parts alkaline regulator, 1 part urea, and 100 parts deionized water.
[0013] The alkaline regulator of this invention is one or more of NaOH, KOH, and LiOH; experiments have shown that using a mixed alkali dissolution method helps to appropriately improve dissolution efficiency and reduce dissolution costs.
[0014] The present invention also provides a method for preparing a wood adhesive based on alkali-dissolved chitosan, comprising: an alkaline dispersion stage, an addition reaction stage, and a coordination crosslinking stage;
[0015] This invention also provides the application of the above-mentioned alkali-soluble chitosan wood adhesive in the preparation of plywood, and the plywood substrate is obtained after gluing, aging, cold pressing and hot pressing processes.
[0016] Furthermore, the single-sided application rate of the adhesive is approximately 130-150 g / m². 2 .
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] (1) This invention employs an alkaline dissolution process to avoid the potential decomposition / corrosion of the wood substrate and metal connectors by the acid system; simultaneously, the alkaline environment enhances the amino reactivity of chitosan and improves the crosslinking efficiency of chitosan, soybean protein, and epichlorohydrin. Anhydrous calcium chloride is introduced to construct a chelating coordination network, which synergistically forms a hydrogen bond and hydrophobic interaction composite system with soybean protein, ultimately constructing a triple network of chemical crosslinking, coordination crosslinking, and physical entanglement. The plywood prepared with the finished adhesive meets the dry / wet strength requirements and fully satisfies the technical requirements of Class II plywood in the national standard (GB / T 9846-2015, ≥0.70MPa).
[0019] (2) The raw materials of this adhesive system do not contain formaldehyde, and there is no formaldehyde release during the entire curing process. It meets the national environmental protection standards for building materials and is safe and harmless in both production and use. With its stable multi-crosslinked structure, the adhesive layer has strong adhesion, good environmental tolerance, and excellent compatibility with various wood-based substrates. It has great potential for application in various artificial board fields such as indoor furniture, decorative boards, and building plywood. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in detail below with reference to specific embodiments, but the scope of protection of this invention is not limited to the following embodiments.
[0021] In the following examples and comparative examples, all raw materials used were commercially available industrial-grade products, and all testing methods used were current national or industry standards.
[0022] Preparation of chitosan alkaline solution:
[0023] Take 3 parts chitosan, 1 part NaOH, 2 parts KOH, 1 part urea, and 100 parts deionized water by weight, mix them, place them in a sealed container, stir and dissolve them at 20°C for 3 hours, and then transfer them to a -20°C environment to freeze for 3 hours. This dissolution-freezing process is recorded as one cycle. Repeat the above cycle 3 times until the chitosan is completely dissolved to obtain a transparent chitosan alkaline solution.
[0024] The preparation scheme of this chitosan alkaline solution uses a mixed alkali of NaOH and KOH as an alkalinity regulator, which has higher dissolution efficiency and lower cost compared with a single alkali. The chitosan alkaline solutions prepared by this scheme are used in the following examples.
[0025] In the chitosan alkaline solution preparation method, the proportions of each component are the same (3 parts chitosan, 1 part NaOH, 2 parts KOH, 1 part urea, and 100 parts water). All examples and comparative examples use the same proportions to prepare the same batch of chitosan alkaline solution.
[0026] The soy protein isolate mentioned in the examples is a commercially available industrial-grade product with a protein content of ≥80% (dry basis) and an isoelectric point of 4.5-5.5. No further purification is required before use.
[0027] The room temperature is 20-30℃.
[0028] Example 1
[0029] This embodiment is the preferred embodiment of the present invention, providing a wood adhesive based on alkali-dissolved chitosan. The wood adhesive is formulated as follows by mass: 30 parts chitosan alkaline solution, 3 parts soy protein isolate, 1 part epichlorohydrin, and 0.5 parts anhydrous calcium chloride.
[0030] The wood adhesive based on alkali-dissolved chitosan is prepared by a method comprising the following steps:
[0031] S1. Alkaline dispersion stage: Add soy protein isolate to the chitosan alkaline solution from step 1, and stir at 40-60℃ for 30-60 minutes to allow the soy protein to fully denature and expand under alkaline conditions, exposing more amino, carboxyl and hydrophobic groups, thus obtaining an alkaline chitosan-soy protein isolate blend.
[0032] S2. Addition reaction stage: Epichlorohydrin is added dropwise to the alkaline chitosan-soybean protein blend obtained in step S1 at a rate of 0.5-2 mL / min, and reacted at 50-70℃ for 1-3 h to obtain a chitosan-soybean protein adhesive with preliminary epichlorohydrin crosslinking. S3. Coordination crosslinking stage: Anhydrous calcium chloride is prepared into a 5-15 wt% aqueous solution and added to the reaction product of step S2. The mixture is stirred at room temperature for 20-40 minutes to prepare a wood adhesive based on a chitosan alkaline solution.
[0033] The technical solution for the application of this embodiment in plywood is as follows:
[0034] The application of the above-mentioned adhesive in plywood preparation includes the following steps:
[0035] In the plywood manufacturing process: adhesive is applied to the surface of veneers, and the veneers are then stacked according to the principle of cross-grain arrangement, followed by hot pressing and curing. The amount of adhesive applied to the veneer surface is 130-150 g / m². 2 The hot-press curing conditions are as follows: first stage: 160℃, 1.1-1.2MPa pressure for 900s; second stage: 160℃, 0.8-0.9MPa pressure for 600s; third stage: 160℃, 0.6-0.7MPa pressure for 720s, to obtain plywood.
[0036] Example 2
[0037] This embodiment provides a wood adhesive preparation based on alkali-dissolved chitosan. The formula, by mass parts, is: 30 parts chitosan alkali solution, 1 part soy protein isolate, 1 part epichlorohydrin, and 0.5 parts anhydrous calcium chloride.
[0038] The preparation method and application process of the adhesive in this embodiment are the same as those in Example 1, except for the formulation parameters.
[0039] Example 3
[0040] This embodiment provides a wood adhesive preparation based on alkali-dissolved chitosan. The formula, by mass parts, is: 30 parts chitosan alkali solution, 3 parts soy protein isolate, 0.5 parts epichlorohydrin, and 0.5 parts anhydrous calcium chloride.
[0041] The preparation method and application process of the adhesive in this embodiment are the same as those in Example 1, except for the formulation parameters.
[0042] Comparative Example 1
[0043] This comparative example provides a wood adhesive preparation based on alkali-dissolved chitosan. The formula, by mass parts, is: 30 parts chitosan alkali solution, 3 parts soy protein isolate, and 1 part epichlorohydrin, without anhydrous calcium chloride.
[0044] The application process of the adhesive in this comparative example is the same as that in Example 1.
[0045] Comparative Example 2
[0046] This comparative example provides a wood adhesive preparation based on alkali-dissolved chitosan. The formula, by mass parts, is: 30 parts chitosan alkali solution, 1 part epichlorohydrin, 0.5 parts anhydrous calcium chloride, and does not contain soy protein isolate.
[0047] The application process of the adhesive in this comparative example is the same as that in Example 1.
[0048] Comparative Example 3
[0049] This comparative example provides a wood adhesive preparation based on acid-dissolved chitosan. The formula, by mass parts, is: 30 parts chitosan acid solution, 3 parts soy protein isolate, 1 part epichlorohydrin, and 0.5 parts anhydrous calcium chloride.
[0050] The chitosan acid solution was prepared by dissolving chitosan using a freeze-thaw method with 2 wt% acetic acid instead of alkali / urea.
[0051] The application process of the adhesive in this comparative example is the same as that in Example 1.
[0052] Comparative Example 4
[0053] This comparative example provides a wood adhesive preparation based on alkali-dissolved chitosan. The formula, by mass parts, is: 30 parts chitosan alkali solution, 3 parts soy protein isolate, 1 part epichlorohydrin, and 0.5 parts anhydrous calcium chloride.
[0054] The chitosan alkaline solution described in this comparative example uses a weak alkaline aqueous solution of sodium bicarbonate instead of the alkali / urea freeze-thaw system of the present invention to dissolve chitosan. Specifically, 100g of a mixed aqueous solution of sodium bicarbonate (0.5 mol / kg) and urea (2 mol / kg) was prepared, and 3g of chitosan was added. The mixture was mechanically stirred at 20°C for 6 hours. The chitosan could not be completely dissolved, and a large amount of insoluble matter remained suspended (the solubility rate was only about 65%). After filtering to remove the insoluble matter, 3g of soybean protein, 1g of epichlorohydrin, and 0.5g of anhydrous calcium chloride were added to the supernatant. After stirring, the mixture was coated onto a plate, and the hot-pressing process was the same as in the preferred embodiment.
[0055] Performance test results
[0056] Physical and chemical properties testing of plywood: In accordance with GB / T 17657--2022 "Test Methods for Physical and Chemical Properties of Wood-based Panels and Decorative Wood-based Panels", the plywood was tested for bonding performance and formaldehyde emission (desiccator method).
[0057] Hydrolysis residue test: In accordance with GB / T 37317-2019 "Determination of hydrolysis resistance of polyurethane adhesives", the hydrolysis residue test was performed on the cured adhesive. The curing conditions were the same as the hot pressing process of the board, and tin foil was used instead of wood veneer.
[0058] Adhesive performance testing: pH test and storage stability test (test period 14 days) were conducted on the adhesives prepared in the examples and comparative examples in accordance with GB / T 14074-2017 "Test methods for adhesives and resins for wood industry".
[0059] The deodorizing agents prepared in Examples 1-3 and Comparative Examples 1-4, and their corresponding particleboards, were tested for performance. The results are shown in Table 1 below:
[0060] Testing items Dry bond strength (MPa) Wet bond strength (MPa) Hydrolysis mass residue rate (%) pH value Formaldehyde release (mg / L) Storage stability (resin viscosity change rate over 14 days, %) Example 1 1.63 1.22 90.2 8.3 0.11 10.2 Example 2 1.54 1.16 83.7 9.4 0.12 7.1 Example 3 1.52 1.09 88.5 8.5 0.10 14.8 Comparative Example 1 1.55 1.13 75.2 8.0 0.11 14.2 Comparative Example 2 1.23 0.93 66.4 10.0 0.15 10.5 Comparative Example 3 1.71 1.12 86.0 1.9 0.13 13.8 Comparative Example 4 0.84 0.27 53.6 8.2 0.12 18.4
[0061] The test results show that:
[0062] The adhesives of Examples 1-3 of this invention all meet the technical requirements for Class II plywood in the national standard (GB / T 9846-2015, ≥0.70MPa) in terms of bonding performance. They successfully replace chitosan acid solution with chitosan alkaline solution in the preparation and application of wood adhesives. The adhesive has a hydrolysis residue rate >80%, and the resin viscosity change rate after 14 days of storage is <20%, with a pH of approximately 8.3-9.4, achieving excellent adhesion to plywood.
[0063] Comparative Example 1, lacking anhydrous calcium chloride, still achieved a dry strength of 1.55 MPa, but its wet strength decreased to 1.13 MPa, with a significant reduction in hydrolysis residue. This indicates that Ca²⁺ coordination crosslinking plays a crucial role in improving water resistance. Comparative Example 2, lacking soy protein isolate, showed a significant decrease in both dry and wet strength and hydrolysis residue, demonstrating the indispensability of the physical entanglement and hydrogen bond network of soy protein. Comparative Example 3, using acid-soluble chitosan, achieved a slightly higher dry strength (1.71 MPa), but with a pH of only 1.9, posing a corrosion risk, and exhibited low wet strength. Comparative Example 4, using a weak alkali system to dissolve chitosan, achieved a solubility of only 65%, resulting in severe degradation of the adhesive properties and failure to meet both dry and wet strength standards. This demonstrates the irreplaceable nature of the specific strong alkali / urea freeze-thaw dissolution system of this invention.
Claims
1. A wood adhesive based on alkali-dissolved chitosan, characterized in that, By weight, it includes: 30 parts chitosan alkaline solution, 1-3 parts soy protein isolate, 0.5-1 part epichlorohydrin, and 0.5 parts anhydrous calcium chloride; Furthermore, the chitosan alkaline solution is prepared by dissolving chitosan in an alkaline regulator and an aqueous urea solution through a 2-5 cycle freeze-thaw process. The components, by mass, are: 1-5 parts chitosan, 2-5 parts alkaline regulator, 1 part urea, and 100 parts deionized water.
2. The wood adhesive according to claim 1, characterized in that, The alkalinity regulator is one or more of NaOH, KOH, and LiOH; the degree of deacetylation of the chitosan is ≥95%, and the viscosity is 100-200 mPa·s; the protein content of the soy protein isolate is ≥80%.
3. The wood adhesive according to claim 1, characterized in that, The pH of the adhesive is 8-10.
4. The wood adhesive based on alkali-dissolved chitosan according to claim 1, characterized in that, The cyclic freeze-thaw cycle lasts for 6 hours at a time, including 3 hours of thawing and 3 hours of freezing. The thawing temperature is 20°C and the freezing temperature is -20°C.
5. The method for preparing the wood adhesive according to any one of claims 1-4, characterized in that, This method includes the following preparation steps: S1. Alkaline dispersion stage: Add soy protein isolate to the chitosan alkaline solution in step 1, and stir at 40-60℃ for 30-60 minutes to allow the soy protein to fully denature and expand under alkaline conditions, exposing more amino, carboxyl and hydrophobic groups, to obtain an alkaline chitosan-soy protein isolate blend. S2. Addition reaction stage: Epichlorohydrin is added dropwise to the alkaline chitosan-soy protein blend obtained in step S1 at a rate of 0.5-2 mL / min, and reacted at 50-70℃ for 1-3 h to obtain a chitosan-soy protein adhesive with preliminary epichlorohydrin crosslinking. S3. Coordination and crosslinking stage: Prepare an aqueous solution of anhydrous calcium chloride at 5-15 wt%, add it to the reaction product of step S2, and stir at room temperature for 20-40 minutes to prepare a wood adhesive based on chitosan alkaline solution.
6. The application of a wood adhesive as described in any one of claims 1-4 in the preparation of plywood, characterized in that, The preparation steps for plywood are as follows: The wood adhesive is applied to the surface of the veneer, and the veneers are stacked according to the principle of cross-grain interlayering and then hot-pressed and cured.
7. The application according to claim 6, characterized in that, The amount of adhesive applied to one side of the coating is 130-150 g / m².
8. The application according to claim 6, characterized in that, After the veneers are stacked, they are subjected to aging, cold pressing and hot pressing processes in sequence; the aging time is 40-60 min; the unit pressure of cold pressing is 0.4-0.6 MPa and the cold pressing time is 60 min.
9. The plywood preparation according to claim 6, characterized in that, The hot-press curing conditions are as follows: hot-press curing at 160-180℃ and 0.6-1.2MPa for 30-40 minutes.
10. The application according to claim 6, characterized in that, For plywood with a thickness of 18 mm, the hot pressing curing adopts a three-stage hot pressing process: the first stage is 160℃, 1.1-1.2 MPa, and pressure held for 900 s; the second stage is 160℃, 0.8-0.9 MPa, and pressure held for 600 s; the third stage is 160℃, 0.6-0.7 MPa, and pressure held for 720 s.
Citation Information
Patent Citations
Basic solvent for dissolving chitosan and method for dissolving chitosan under alkaline condition
CN102634040A
Gel prepared from chitosan or chitosan derivatives by multi-crosslinking and preparation method
CN107325306A
Preparation method of chitosan gel material
CN111518305A